Peran Informal Keluarga terhadap Kemampuan Anak Usia Toddler Mengatur Toilet Training di Desa Prekbun Kecamatan Pademawu Kabupaten Pamekasan - Dina Novarita Kusuma Wardani (Ovary Midwifery Journal, 2019)
The role of the family is needed to support the successful implementation of Toilet Training. One method that can be done by parents to children by using the technique of stretching and modeling techniques. The purpose of this study was to determine the relationship of informal family roles to the ability of toddlers to arrange toilet training in Prekbun Village, Pademawu District, Pamekasan Regency. The type of this research uses an analytical method with a cross sectional approach. The population taken was families who had toddler age children in Prekbun Village, Pademawu Subdistrict, Pamekasan Regency, as many as 159 respondents. The sampling technique used simple random sampling, so that there were 110 respondents. Data collecting using a quetionnaire. Then the results are tabulated and analyzed using Chi Square test. The results showed that 110 respondents had a good informal role (62%) and children were able to arrange toilet training (65%), while families with informal roles were quite large (24%) and children were unable to arrange toilet training (35%), and a small proportion of families have less informal roles (14%) and children cannot manage toilet training (35%). After the data was analyzed using the Chi-square test, it was obtained χ2 counts greater than χ2 tables, thus H1 was accepted, which means that there is a relationship between the informal role of the family and the ability of toddlers to arrange toilet training. Families must provide an intensive approach to children to train them to the toilet, after that they consistently run it later, because the success of toilet training is inseparable from the readiness of the child itself but good cooperation between the family.